Neural basis of anticipatory anxiety reappraisals. - Shinpei Yoshimura (Public Library of Science (PLoS), 2014)
Reappraisal is a well-known emotion regulation strategy. Recent neuroimaging studies suggest that reappraisal recruits both medial and lateral prefrontal brain regions. However, few studies have investigated neural representation of reappraisals associated with anticipatory anxiety, and the specific nature of the brain activity underlying this process remains unclear. We used functional magnetic resonance imaging (fMRI) to investigate neural activity associated with reappraisals of transient anticipatory anxiety. Although transient anxiety activated mainly subcortical regions, reappraisals targeting the anxiety were associated with increased activity in the medial and lateral prefrontal regions (including the orbitofrontal and anterior cingulate cortices). Reappraisal decreased fear circuit activity (including the amygdala and thalamus). Correlational analysis demonstrated that reductions in subjective anxiety associated with reappraisal were correlated with orbitofrontal and anterior cingulate cortex activation. Reappraisal recruits medial and lateral prefrontal regions; particularly the orbitofrontal and anterior cingulate cortices are associated with successful use of this emotion regulation strategy.